THEORY SEVERAL FIELDS - Adina TĂTAR (Journal of Research and Innovation for Sustainable Society, 2020)
The basic theoretical framework particle physicists use to describe the behavior of relativistic quantum systems is Quantum Field Theory. In the modern framework of the quantum theory of fields, even without referring to a test particle, a field occupies space, contains energy, and its presence precludes a classical "true vacuum". This has led physicists to consider electromagnetic fields to be a physical entity, making the field concept a supporting paradigm of the edifice of modern physics. Field theory usually refers to a construction of the dynamics of a field, i.e. a specification of how a field changes with time or with respect to other independent physical variables on which the field depends.